Variation in mouse pelvic morphology maps to locations enriched in Sox9 Class II and Pitx1 regulatory features. Issue 2 (3rd February 2020) - Roseman, Charles C.; Capellini, Terence D.; Jagoda, Evelyn; Williams, Scott A.; Grabowski, Mark; O'Connor, Christine; Polk, John D.; Cheverud, James M.
Abstract: Variation in pelvic morphology has a complex genetic basis and its patterning and specification is governed by conserved developmental pathways. Whether the mechanisms underlying the differentiation and specification of the pelvis also produce the morphological covariation on which natural selection may act, is still an open question in evolutionary developmental biology. We use high‐resolution quantitative trait locus (QTL) mapping in the F34 generation of an advanced intercross experiment (LG, SM‐G34 ) to characterize the genetic architecture of the mouse pelvis. We test the prediction that genomic features linked to developmental patterning and differentiation of the hind limb and pelvis and the regulation of chondrogenesis are overrepresented in QTL. We find 31 single QTL trait associations at the genome‐ or chromosome‐wise significance level coalescing to 27 pleiotropic loci. We recover further QTL at a more relaxed significance threshold replicating locations found in a previous experiment in an earlier generation of the same population. QTL were more likely than chance to harbor Pitx1 and Sox9 Class II chromatin immunoprecipitation‐seq features active during development of skeletal features. There was weak or no support for the enrichment of seven more categories of developmental features drawn from the literature. Our results suggest that genotypic variation is channeled through a subset of developmental processes involved in the generation of phenotypic variation in the pelvis. This finding indicates that the evolvability of complex traits may be subject to biases not evident from patterns of covariance among morphological features or developmental patterning when either is considered in isolation. Abstract : Variation in aspects of the morphology of the mouse pelvis maps to various locations across the genome. These regions are enriched for some classes of regulatory features known to be involved in the development of cartilage and bone. Research Highlights: Pelvic variation maps to locations in the genome that are enriched in for Sox9 Class II and Pitx1 features. Few genes previously implicated as playing a core role in the development of the pelvis occur in mapped intervals.